SASAK COMMUNITY'S COMMUNICATIVE ACT IN NGELUKAR AND NGILAHAN KAOQ RITE IN LOMBOK - Suparman Jayadi; Ratih Rahmawati (al-Balagh : Jurnal Dakwah dan Komunikasi, 2020)
The Ngelukar and Ngilahan Kaoq rite are religious and cultural ceremonies performed by Balinese Hindus and Sasak Muslims in Lingsar Village. The aim of this study is to analyze the communicative actions of the Sasak people in the Ngelukar and Ngilahan Kaoq rite as interethnic socio-cultural integration. This research used qualitative methods with a case study design and the data were collected through observation, in-depth interviews, and documentation. The analysis used Habermas's theory of communicative action. The results showed that both Hindus and Muslims through this ritual could build the concept of interfaith togetherness, which is actualized for survival. Through the social communication, this can shape the actions to maintain the tradition of both adherents (Hindu and Muslim) according to the prevailing rules and values in the Ngelukar and Ngilahan Kaoq rituals. This ritual activity is a form of the communicative rationality actions by the Sasak people.